Nuclear and Cytoskeletal Prestress Govern the Anisotropic Mechanical Properties of the Nucleus - Macadangdang, Joan Karla (Université d'Ottawa / University of Ottawa, 2012)
Physical forces in the cellular microenvironment play an important role in governing cell function. Forces transmitted through the cell cause distinct deformation of the nucleus, and possibly play a role in force-mediated gene expression. The work presented in this thesis drew upon innovative strategies employing simultaneous atomic force and laser-scanning confocal microscopy, as well as parallel optical stretching experiments, to gain unique insights into the response of eukaryotic cell nuclei to external force. Non-destructive approaches confirmed the existence of a clear anisotropy in nuclear mechanical properties, and showed that the nucleus' mechanical response to extracellular forces is differentially governed by both nuclear and cytoskeletal prestress: nuclear prestress regulates shape and anisotropic deformation, whereas cytoskeletal prestress modulates the magnitude and degree of deformation. Importantly, the anisotropic mechanical response was conserved among diverse differentiated cell types from multiple species, suggesting that nuclear mechanical anisotropy plays an important role in cell function.
Keywords: nucleus; eukaryotic cell; atomic force microscopy; confocal microscopy; optical stretcher; cytoskeleton; force transduction; anisotropy